2018
DOI: 10.2147/ott.s155581
|View full text |Cite
|
Sign up to set email alerts
|

The role of bevacizumab in targeted vascular endothelial growth factor therapy for epithelial ovarian cancer: an updated systematic review and meta-analysis

Abstract: The impact of bevacizumab (an anti-vascular endothelial growth factor therapy) remains uncertain, which has been the focus of studies on the management of epithelial ovarian cancer (EOC). To investigate the efficacy of bevacizumab combinations with different regimens in the treatment of patients with EOC, a meta-analysis of Phase III randomized controlled trials was conducted. The databases searched included PubMed, Embase, ClinicalTrials.gov, Chinese Knowledge Infrastructure, as well as the Cochrane Central R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Another meta-analysis by Ruan et al, demonstrated an improvement in PFS (HR 0.63; p=<0.01), and OS (HR 0.91 p=<0.05). These pooled results suggest an OS benefit for bevacizumab treatment in the maintenance setting, but at a level that would be of impact in very few patients given the HR of 0.91 54 .…”
Section: Targeted Molecular Therapiesmentioning
confidence: 87%
“…Another meta-analysis by Ruan et al, demonstrated an improvement in PFS (HR 0.63; p=<0.01), and OS (HR 0.91 p=<0.05). These pooled results suggest an OS benefit for bevacizumab treatment in the maintenance setting, but at a level that would be of impact in very few patients given the HR of 0.91 54 .…”
Section: Targeted Molecular Therapiesmentioning
confidence: 87%
“…Bevacizumab, a human monoclonal antibody against VEGF, is currently used to treat tumors such as lung adenocarcinoma, [22] colorectal cancer, [23] and ovarian cancer. [24] However, clinical trials of bevacizumab for treating SCLC revealed that the treatment did not prolong survival. The ECOG3501 trial validated the efficacy and safety of the combination of IP and bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
“…5 Consistent ly, VEGF inhibition by bevacizumab in combination with chemotherapy, followed by maintenance therapy, has proven effective in delaying disease progression in ovarian cancer when administered after initial surgical resection or in recurrent platinumsensitive disease, and as monotherapy or combined with chemotherapy in patients with platinum-resistant disease. [6][7][8] However, various mechanisms may allow escape of tumor cells from therapeutic control, including selection of tumor clones with increased expression of compensatory signaling pathways or clones with an increased capacity to grow and invade normal tissues in conditions of limited angiogenic support. 9,10 Multiple approaches are thus being investigated to further improve clinical outcomes, through the development and characterization of novel antiangiogenic agents, and their use in combination regimens with agents targeting other key pathways in tumor cells (i.e.…”
Section: Angiogenesis and Vascular Endothelial Growth Factor Receptormentioning
confidence: 99%